Study of MARA University of Technology (UiTM) students’ willingness to contribute in Private Retirement Scheme Youth Incentive / Qurratu ‘Aini Syazwani Rahman Hadzari - Rahman Hadzari, Qurratu ‘Aini Syazwani (Universiti Teknologi MARA, Selangor, Puncak Alam Campus, 2018)
Private Retirement Scheme Youth Incentive officially implemented by government on 2014 with the aim to attract and encourage more youths to involve in long term investment in Private Retirement Scheme. The main objectives of this study are to review the background of PRS product and its affiliated matters, to examine the students’ level of awareness of PRS Youth Incentive and willingness to contribute in it. This study applies quantitative approach with the use of survey questionnaires as the main instrument of data collection. Students from UiTM Puncak Alam, Selangor were selected as respondents of this study. Data collected was analysed using descriptive analysis. In general, finding of this study shows that the level of awareness of students toward PRS Youth Incentive is only at moderate level as well as their willingness to contribute in it.